If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(v + -7) + 5v = 28 Reorder the terms: 2(-7 + v) + 5v = 28 (-7 * 2 + v * 2) + 5v = 28 (-14 + 2v) + 5v = 28 Combine like terms: 2v + 5v = 7v -14 + 7v = 28 Solving -14 + 7v = 28 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 7v = 28 + 14 Combine like terms: -14 + 14 = 0 0 + 7v = 28 + 14 7v = 28 + 14 Combine like terms: 28 + 14 = 42 7v = 42 Divide each side by '7'. v = 6 Simplifying v = 6
| (x+1)(x-2)/x+3 | | 2(x+4)+3*x=-12 | | 7*y+23=4*y+8*y-22 | | x/5-12=4 | | -8=5x+3 | | k(2)-25=0 | | 2y+3=(y+21) | | 6*y+5=8*y+11 | | 28+19*x=-8+15*x | | 6x+8=11-4c | | -83=2*v-15*v-18 | | x+x+6x=119+6x | | 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 | | 4*x+43+2*x=7 | | (0.3+2x)(0.5+2x)=5.3018 | | -9*x-2*x-18=26 | | 108+(5x+8)=x | | -(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | x/2+x/4+x/5=x-1 | | w*5-7+w*2=-17 | | 3*3=8 | | 48-54+30= | | 63x^2-24x-15=0 | | -9(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | q^2+4q+4=26 | | 6-+4=210 | | 3x+20=5-16 | | (3x-4)(x-3x+2)= |